Inovasi Manajemen Kinerja Guru dalam Meningkatkan Mutu Pendidikan di MI. Kahasri Kota Probolinggo - Suef Priyanto; Nurul Hidayah (Syntax Corporation, 2023)
Education is one of the pillars of a country's development. Teachers as central figures in the education system have a very important role in improving the quality of education. Innovation in teacher performance management is the key to improving the quality of education. This research examines effective innovations in teacher performance management to improve the quality of education. This research uses a qualitative research method with a case study approach at Madrasah Ibtidaiya Kahasiri, Probolinggo City. Data was collected through interviews with teachers, classroom observations, and analysis of documents related to teacher performance management. This study shows that effective innovation in teacher performance management includes several main aspects. First, inclusive and collaborative leadership development helps create a positive work environment. Leadership that understands and supports teachers' needs and supports their professional development plays a key role in increasing teacher morale and motivation. Second, teacher empowerment through training and skills development aims to improve pedagogical competence and classroom management skills. Third, the use of information and communication technology (ICT) in education and teacher performance management can increase the efficiency and effectiveness of the learning process. The results of this research indicate that effective innovation in teacher performance management requires collaboration between school principals, teachers and other stakeholders. Creating a positive work environment, empowering teachers, and using technology wisely can significantly improve the quality of education. Therefore, education stakeholders are expected to adopt these innovations to improve the quality of education and provide a better future for future generations.